The discriminative ability of the triglyceride-glucose index to identify metabolic syndrome among adults of the northern Sri Lankan population - Paramanathan, T.; Sandrasegarampillai, B.; Arasaratnam, V.; Thirunavukarasu, K. (Research gate, 2024)
Background The triglyceride-glucose index (TyG index) is a simple surrogate marker for Insulin Resistance (IR). How- ever, the relationship between the TyG index and Metabolic Syndrome (MetS) remains unknown in the Northern Sri Lankan population. Methods This was a descriptive, cross-sectional study of adults aged between 18 and 65 years living in Jafna, Sri Lanka. This study aimed to verify the discriminative ability of the TyG index to identify MetS using the International Diabetes Federation (IDF-2006) criteria and to determine the gender-specifc TyG index cut-of values for better prediction of MetS in Northern Sri Lankan adults. TyG index was calculated as Ln[Triglycerides (TG) (mg/dl)×Fasting plasma glucose (FPG) (mg/dl)/2]. Results A total of 540 individuals were included in this study, with a mean age of 42.18 (±13.89) years for males and 43.80 (±12.56) years for females. The mean value of the TyG index in the total study population was 8.54 (±0.53). Individuals in the higher quartiles of the TyG index had a signifcantly increased risk of MetS compared with those in the lowest quartile (p<0.01). TyG index showed a stronger association with MetS than the FPG and all the conven- tional lipid components and the unadjusted odds ratio was 5.47. The area under the curve (AUC) of ROC revealed values of 0.914 (95% confdence interval (CI): 0.884, 0.944) for females, 0.881 (95% CI: 0.830, 0.932) for males and 0.897 (95% CI: 0.870, 0.924) for the total study population. TyG index had a stronger discriminative ability to identify MetS as per IDF criteria in the study population with a cut-of value of 8.60. The mean level of the TyG index signifcantly increased with the increasing number of MetS components. Conclusions The mean value of the TyG index increased as the number of MetS components in the study popu- lation increased. Individuals with a higher TyG index had a signifcantly increased risk of having MetS compared with the lowest quartile of the TyG index. TyG index had a good discriminative ability to diagnose MetS as per IDF criteria among the northern Sri Lankan population.
Keywords: Triglyceride-glucose (TyG) index; Metabolic syndrome; Prevalence; Sri Lanka